The Interactive Effect of Tonic Pain and Motor Learning on Corticospinal Excitability - Erin Dancey; Paul Yielder; Bernadette Murphy (Brain Sciences, 2019)
Prior work showed differential alterations in early somatosensory evoked potentials (SEPs) and improved motor learning while in acute tonic pain. The aim of the current study was to determine the interactive effect of acute tonic pain and early motor learning on corticospinal excitability as measured by transcranial magnetic stimulation (TMS). Two groups of twelve participants (n = 24) were randomly assigned to a control (inert lotion) or capsaicin (capsaicin cream) group. TMS input–output (IO) curves were performed at baseline, post-application, and following motor learning acquisition. Following the application of the creams, participants in both groups completed a motor tracing task (pre-test and an acquisition test) followed by a retention test (completed without capsaicin) within 24–48 h. Following an acquisition phase, there was a significant increase in the slope of the TMS IO curves for the control group (p < 0.05), and no significant change for the capsaicin group (p = 0.57). Both groups improved in accuracy following an acquisition phase (p < 0.001). The capsaicin group outperformed the control group at pre-test (p < 0.005), following an acquisition phase (p < 0.005), and following a retention test (p < 0.005). When data was normalized to the pre-test values, the learning effects were similar for both groups post-acquisition and at retention (p < 0.005), with no interactive effect of group. The acute tonic pain in this study was shown to negate the increase in IO slope observed for the control group despite the fact that motor performance improved similarly to the control group following acquisition and retention. This study highlights the need to better understand the implications of neural changes accompanying early motor learning, particularly while in pain.